Temperature and Humidity Monitoring System on Android Based Wallet House - Ronny; Salmon; Ahmad Rofiq Hakim (Politeknik Pertanian Negeri Samarinda, 2021)
The quality and quantity of swallow's nest is strongly influenced by temperature and humidity. By utilizing Wifi, users can monitor room temperature and humidity in the swallow house remotely with the Android system. The Android system can make it easier for users to monitor room temperature and humidity in the swallow house at any time. DHT11 sensor which functions as a temperature and humidity detector, NodeMCU ESP8266 microcontroller which functions as a data processor so that the DHT11 sensor detection results can be displayed on a Smartphone via the Blynk application so that users can see directly the results of temperature and humidity measurements in the swallow house room. This research was conducted in Pulau Lanting Village, Jempang District, West Kutai Regency. The data collection methods used are literature study, interviews, and observation. While the system development method used is Waterfall. As well as the supporting software used by the Arduino Integrated Development Environment, and Blynk.